SISTEM KENDALI DUAL MOTOR PROPELLER PADA ALAT SELF BALANCING MENGGUNAKAN KONTROLER PID DENGAN TUNING CHR - Farid . Baskoro; Prayuda Ari Guntoro; Muhamad Syariffuddien Zuhrie; Bambang . Suprianto; I Gusti Putu Asto Buditjahjanto (Universitas Negeri Surabaya, 2021)
Abstract Unmanned Aircraft or known as UAV (Unmanned Aerial Vehicle) is a vehicle that does not have a crew, which in the last decade has been developed by researchers, students and technology companies. Multirotor included in one type of vehicle that has the ability to take off vertically and be able to maintain its position when flying. In flying a Multirotor sometimes it takes a stable height to carry out certain missions. The problem with Multirotor is the balance of flight when the load on the Multirotor is not balanced. The purpose of this research is to design a smaller scale Multirotor used to produce a stable system using a PID controller with the CHR method so that this method is expected to be applied later on a larger Multirotor vehicle. The results of the implementation simulation using the Proportional Integral Derifative (PID) controller on the self balancing control system on the Dual Motor Propeller obtained the best value Kp = 9.01 Ki = 0.52 and Kd = 0.13 can improve the system response with Ess = 0.99% Maximum overshoot = 3.13% td = 2.45 s, tr = 3.95 s, ts (5%) = 0.75 s.